Gas Sensor Devices based on CuO- and ZnO- Nanowires directly synthesized on silicon substrate. Issue 13 (2016) - Wimmer-Teubenbacher, R.; Lackner, E.; Krainer, J.; Steinhauer, S.; Koeck, A.
ABSTRACT: In-situ grown CuO and ZnO nanowire (NW) arrays were evaluated for their gas sensing performance. The metal structures were fabricated by standard e-beam lithography, thermal evaporation and lift-off process onto a silicon substrate with gold electrodes. After integration onto a test structure with resistive heater and thermocouple for temperature control, the samples were thermally oxidized at 400°C. During thermal oxidation, nanowires were grown between the oxidized metal structures. The gas sensing performance of the NW array was tested for carbon monoxide, - and a hydrocarbon-mixture (acetylene, ethane, ethene, and propene) at three relative humidity levels.